Singing Formula of Kelong Jaga (Kajang Oral Tradition) - A. Tenrinia Asmanur (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study focuses on the formula of Kelong Jaga. This study used a descriptive qualitative method in which data were the lyrics of Kelong Jaga then analyzed based on theory of Lord (1981). The result shows that singers of Kelong Jaga use ready common repeated pattern from tradition but in some certain part they usually have to improvise the lyric. The way of learning of Kelong Jaga starts from listening the performance in every opportunity, then practicing in leisure time, and finally trying to get the opportunity to perform in front of the real audience. The formula is distinguished in some parts, namely line analysis, parallel sense, and filler occurred in the Kelong Jaga. It is involved by some ideas that generally mean having good attitude to others, as a guest and as a host. It is involved some ideas namely, 1) Respecting ada’; 2) Party or feast; 3) Telling story about a single girl; 4) Unity and kinship; 5) Giving the best service to the guest; 6) Acting the best attitude to the host; and 7) Keeping earth or environment. It is suggested to youth to learn and perpetuate kelong jaga as oral tradition in Kajang community, thus extinction threat could be avoided. Keywords: Singing formula, Kelong Jaga, oral tradition, Kajang community.